The Influence of Social Aspects on the Behavior of the Main Figures in the Novel â€œSer! Randha Cocakâ€ (Universitas Negeri Semarang, 2019)
Literature is born, grows, and lives and develops in society. The influence of the writing for the reader can occur in past readers and today's readers.Through this research, we can learn how to behave or face certain characters in life in society. This studywasconductedwith the aim of describing the influence of social aspects on the behavior of the main character in the novel â€œSer! Randha Cocakâ€by Suparto Brata, namely Javanese culture and western culture, social love, and economic problems of poverty. This study was conductedwith qualitative descriptive, analytical methods that were sourcedfrom the novel.The study data is in the form of discourse fragments which are thought to contain the influence of social aspects on the behavior of the main characters in the novel â€œSer! Randha Cocakâ€by Suparto Brata by using library techniques, then the data was analyzed using heuristic and hermeneutic reading techniques.The results show that Javanese culture considers the lineage of boys as important and arranged marriage tends to be doneso that their children get a good partner. In the social aspect, the love of siblings and spouses makes the leaders help each other, defend, and fight for their enjoyment. Poverty makes leaders, Dororini and Surahanado various ways to achieve their goals to plan a murder. The results of this study are useful for students to know the values contained in a novel, able to sort out the positive and negative sides of thebook and can be used as a material for self-evaluation and attitude in social life.